MANAJEMEN KURIKULUM PESANTREN LANSIA (STUDI KASUS DI PESANTREN LANSIA AL HIKMAH CIBUNGBULANG BOGOR) - Ali, Agus; Haetami , Pikri Al (Universitas Wiralodra, 2025)
Abstract In the development of human civilization, education has experienced significant and continuous progress, extending throughout life. The concept of lifelong education in the Islamic perspective emphasizes the importance of learning without age limits, including for the elderly. This study aims to analyze curriculum management in improving the quality of elderly pesantren education, with a case study at Pesantren Lansia Al Hikmah Cibungbulang, Bogor. This research employs a descriptive qualitative method with a case study approach. The research subjects include leaders, educators, and students of the pesantren. Data were collected through observation, interviews, and documentation, and analyzed through three stages: data reduction, data presentation, and conclusion drawing. The findings of the study reveal that: (1) Curriculum planning based on spiritual values at Pesantren Lansia Al Hikmah applies the learner-centered design concept with an existentialist philosophical approach, emphasizing the development of students as the central focus of learning. (2) Curriculum implementation employs a direct learning system model and andragogical approach, encompassing learning activities and evaluations through tests on *tahsin*, *tahfiz*, *Juz Amma*, and worship practices. (3) Curriculum management evaluation based on spiritual values is conducted using the CIPP model (Context, Input, Process, Product). In conclusion, curriculum management based on spiritual values at Pesantren Lansia Al Hikmah has proven effective in improving the quality of elderly education through integrated planning, implementation, and evaluation. Keywords: lifelong education, curriculum management, elderly pesantren.